DIVERSet JAG compounds inhibit topoisomerase II and are effective against adult and pediatric high-grade gliomas - Howarth, Alison (2020)
High-grade gliomas (HGGs) are aggressive primary brain tumors with local invasive growth and poor clinical prognosis in both adult and pediatric patients. Clinical response is compounded by resistance to standard frontline antineoplastic agents, an absence of novel therapeutics, and poor in vitro models to evaluate these. We screened a range of recently identified anticancer compounds in conventional adult, pediatric, and new biopsy-derived HGG models. These in vitro lines showed a range of sensitivity to standard chemotherapeutics, with varying expression levels of the prognostic markers hypoxia-induced factor (HIF) 1α and p53. Our evaluation of lead DIVERSet library compounds identified that JAG-6A, a compound that was significantly more potent than temozolomide or etoposide, was effective against HGG models in two-dimensional and three-dimensional systems; mediated this response by the potent inhibition of topoisomerase Iiα; remained effective under normoxic and hypoxic conditions; and displayed limited toxicity to non-neoplastic astrocytes. These data suggest that JAG-6A could be an alternative topoisomerase IIα inhibitor and used for the treatment of HGG.